1966
DOI: 10.1080/00268976600100421
|View full text |Cite
|
Sign up to set email alerts
|

Zero-field splittings in aromatic triplet states

Abstract: The zero-field splitting parameters of the triplet state, D, E and D*, have been calculated in the two configuration approximation for the hydrocarbons pyrene and 1,12-benzperylene, and the results compared with the experiment. For calculations on molecules of this size it is a reasonable approximation to neglect two centre dipolar interaction integrals between 7r-electron centres more than 12 Bohr radii apart. Results in a one configuration approximation for the naphthalene molecule using open sheU-SCF-MO's a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1968
1968
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Lifetimes of spin excited states in organics are substantially longer than inorganic materials, microseconds instead of pico or nanoseconds [41]. In some aromatic molecules, lifetimes have been observed as high as milliseconds or even full seconds [42][43][44][45]. The long lifetime in organics is due to the weak spin-orbit coupling (SOC), as a result of the low molecular weight of the materials involved, such as carbon and hydrogen in small molecule arrangements (low Z value) or π-conjugated polymers [41].…”
Section: Organic Masersmentioning
confidence: 99%
“…Lifetimes of spin excited states in organics are substantially longer than inorganic materials, microseconds instead of pico or nanoseconds [41]. In some aromatic molecules, lifetimes have been observed as high as milliseconds or even full seconds [42][43][44][45]. The long lifetime in organics is due to the weak spin-orbit coupling (SOC), as a result of the low molecular weight of the materials involved, such as carbon and hydrogen in small molecule arrangements (low Z value) or π-conjugated polymers [41].…”
Section: Organic Masersmentioning
confidence: 99%
“…When the 7rt's are expressed as linear combinations of atomic orbitals, ir¡ = \ , D becomes D = (3g^2/4Aca02)| (^ariatiasjauj X (X,(l)Xs( 2)|(ri22 -3zi2>12-6|X,(1)X"(2)) + ariautas¡atj X (Xr(l)Xs( 2)[(r122 -3zi22)nr5|X"(l)Xi(2)]» (9) where <X,(l)Xs( 2)|(r122 -3z122)r12-s|Xi(l)Xu( 2)) are the atomic orbital dipole interaction integrals8 for Slater 2 orbitals with Z = 3.18; C-C distance, 1.40 A;…”
Section: Zero Field Splitting Parametermentioning
confidence: 99%
“…The dominant factor in determining the ZFS of organic, heavy element free molecules is the electron SSC, and the contribution of SOC is usually negligible. Early studies of the electron SSC in aromatic molecules were performed using semiempirical approaches. However, the first calculation of ZFS parameters of triplet benzene using the ab initio configuration interaction (CI) method performed by Langhoff revealed that the comparative agreement with the experimental values in the semiempirical calculation was coincidental . It was also pointed out that the calculation of ZFS parameters was technically difficult because a reliable description of spin density required a large number of configurations including in CI space, which was computationally too demanding at that time.…”
Section: Introductionmentioning
confidence: 99%